Human behavior in organizations - Martires, Conception Rodil (Mandaluyong City, 2010)
This book is a product of the desire to come up with a teaching material on human behavior that contains not only theoretical constructs but also caselets, cases, games, group dynamics exercises, program contents for short seminars and summaries of relevant research studies in the Philippines.
Keywords: organizational behavior